EDUCATION MANAGEMENT EFFORTS IN CONDUCTING DERADICALIZATION BOARDING (Study In The Village of Tenggulun Subdistrict Solokuro Lamongan East Java Province) - SETIOBUDI, EKO (Jurnal Ilmiah Educational Management, 2016)
This research was aimed to know the background of the rise of radicalism once portray the role of Education Management in order reduced the radical movement, especially in the village of Tenggulun Subdistrict Solokuro Lamongan East Java Province. Research using qualitative approach and grounded theory method.Analysis of data using open coding, data collection technique through interview, observation and document analysis. Sources of data obtained through informants, photos and documents. Results of the study: (1) Poverty and lack of education to be one factor in the rise of radical ideologies Tenggulun. This adversely affects the control of the public of the existence of Pesantren Al Islam, which has a different aqidah, (2) after the Bali bombings, Pesantren Al Islam to change the orientation of education, of jihad, preaching and tarbiyah, be tarbiyah, propaganda and jihad. And implemented in Education Management at Al Islam, (3) other changes to transform the military into a jihad jihad moderate implemented through propaganda to the people around, with patterns of acculturation, through Muhammadiyah, and are involved in de-radicalization activities. Recommendations research is further increasing socialization of political education, government to embrace more radical schools to engage in de-radicalization and need further research on the relationship between Muhammadiyah and Islamic Aqeedah pure and devout.